The Democrats' Opportunity: Are They Ready? - Faux, Jeff (Dissent (0012-3846))
This article critically analyses the political strategy of the democrats in the U.S. The author observes that Democratic leaders, in and out of power have constantly ceded ideological territory in the hopes that the right will overreach. The author recalls that waiting for the Republican party's mistake has been occasionally successful for the democrats. Democrat Bill Clinton won the 1992 election because candidate Ross Perot, split the Republican constituency and Republican George H.W. Bush, angered voters with his indifference to rising unemployment. The article discusses the economic policy of the U.S. and the large scale problems faced by the country. The article also discusses the book "Pro-Growth Progressive" by Gene Sperling.